The Diverse Genomic Landscape of Diamond-Blackfan Anemia: Two Novel Variants and a Mini-Review - Iordanis Pelagiadis; Ioannis Kyriakidis; Nikolaos Katzilakis; Chrysoula Kosmeri; Danai Veltra; Christalena Sofocleous; Stavros Glentis; Antonis Kattamis; Alexandros Makis; Eftichia Stiakaki (MDPI AG, 2023)
Diamond-Blackfan anemia (DBA) is a ribosomopathy characterized by bone marrow erythroid hypoplasia, which typically presents with severe anemia within the first months of life. DBA is typically attributed to a heterozygous mutation in a ribosomal protein (RP) gene along with a defect in the ribosomal RNA (rRNA) maturation or levels. Besides classic DBA, DBA-like disease has been described with variations in 16 genes (primarily in GATA1, followed by ADA2 alias CECR1, HEATR3, and TSR2). To date, more than a thousand variants have been reported in RP genes. Splice variants represent 6% of identifiable genetic defects in DBA, while their prevalence is 14.3% when focusing on pathogenic and likely pathogenic (P/LP) variants, thus highlighting the impact of such alterations in RP translation and, subsequently, in ribosome levels. We hereby present two cases with novel pathogenic splice variants in RPS17 and RPS26. Associations of DBA-related variants with specific phenotypic features and malignancies and the molecular consequences of pathogenic variations for each DBA-related gene are discussed. The determinants of the spontaneous remission, cancer development, variable expression of the same variants between families, and selectivity of RP defects towards the erythroid lineage remain to be elucidated.